Expertise-related differences in the performance of simple and complex tasks: An event-related potential evaluation of futsal players - Duncan, S.; Oppici, L.; Borg, C.; Farrow, D.; Polman, R.; Serpiello, F. R. (Science and Medicine in Football, 2018)
Background: In recent years, anecdotal evidence has pointed to the importance of futsal as a significant activity for the development of perceptual and technical skills, possibly due to the intensity of the game providing a multitude of different stimuli to the players. However, no scientific evidence to date exists regarding the processes that may underpin such benefits. The purpose of this study was to assess differences in electro-cortical activity and reaction time (RT) between expert and recreational futsal players. Methods: 11 expert and 12 recreational futsal players (mean age: 28.7 ± 4.9 years) performed congruent and incongruent trials of a modified Flanker task on a customised computer screen. RT generated by an index-finger mouse press was recorded via a customised micro-processing system and electro-cortical activity was recorded by electroencephalography during task performance. Results: There was a significant difference in RT and error rate in congruent and incongruent task performance, and difference in electro-cortical activity showing an enhanced N1 ERP mean amplitude within the parietal region in the expert compared to recreational group. Conclusion: Similar to previous research, a greater level of expertise leads to recruitment of brain areas necessary for the efficient integration and processing of information required to produce desired goal-directed behaviour.